A comparative online survey on the intention to get COVID-19 vaccine between Greek and Cypriot healthcare personnel: is the country a predictor? - Vasilios Raftopoulos; Stelios Iordanou; Angeliki Katsapi; Xanthi Dedoukou; Helena C. Maltezou (Taylor & Francis Group, 2021)
Vaccine hesitancy amongst healthcare personnel (HCP) is a critical issue. The aim was to explore the factors that determine the intention to opt for COVID-19 vaccine among HCP from two southern European countries. An anonymous online self-administered survey using Google Forms has been conducted between December 1st to December 15th, 2020 among the HCP in Greece and the Republic of Cyprus. A total of 2,238 HCPs participated in the study (1,220/54.5% from Republic of Cyprus and 1,018 from Greece). Overall 1,082 (48.3%) stressed their intention to get vaccinated (64.4% for Greece and 34.9% for Republic of Cyprus). The main reasons for those who intend to get the COVID-19 vaccine include self (94.2%), family (98.7%), and patients protection (95.2%) as well as mitigation of COVID-19 pandemic (95.4%). The multivariate logistic regression that was performed for the total sample revealed that the following variables were significantly associated with an increased probability to get vaccinated against COVID-19: being a physician, a member of the nursing personnel, paramedical staff, working in Greece, age, the belief that influenza vaccination should be mandatory for HCP, and the rating of the overall management of COVID-19 pandemic in the country and from the public hospitals. Physicians were more likely to get vaccinated against COVID-19 than other HCP. The age was a predictor of COVID-19 uptake intention in the Republic of Cyprus. The belief that there was a successful management of the COVID-19 pandemic contributed to the intention to COVID-19 vaccination uptake.